"But I'm not a racist!" Phenomenology, racism, and the body schema in white, pre-service teacher education. Issue 1 (2nd January 2018) - Lewis, Tyson E.
Abstract: In this article, I call for a phenomenological turn in educating white, pre-service teachers. As opposed to dominant pedagogical models which focus on changing one's beliefs about race, phenomenology points toward the importance of pre-conceptual, pre-critical forms of racial embodiment. Here I draw upon recent work on the different between body image (beliefs about the body) and body schema (what the body can do). The worry is that existing forms of anti-oppressive education miss the centrality of the schema, and thus do not go far enough in uncovering the embodied, perceptual roots of racism.